Prediction of Peak VO2 Values From 9-Minute Run Distances in Young Males, 9-14 Years - Baldwin, Deborah Lynn (My University, 1983)
Thirty young male volunteers, 9-14.yrs, were studied to determine if a relationship existed between peak VO2 and the 9-min run distance. Physical characteristics for a1l Ss included ht, wt, and % fat. Ss were tested for volitional peak VO2 on the treadmill using the Skinner et al. (1971) protocol. Variables measured were VE max, RER, HR max, and peak VO2 (l-min -1 ml/kg/min-l). A 9-min run for distance was also performed by the Ss. A multiple regression technique was used to predict peak 90 from the 9-min run distance. The resulting r value when predicting peak VO2 in ml/kg/min from the 9-min distance was 0.693. The r value for prediction of peak VO2 in l'min from the 9-min run distance was 0.583. Other variables measured were entered into the regression technique to improve the R such as age, ht, wt, HR, F3R, % fat, and body density. It was concluded that 2 equations which utilized . wt (kg) and ht (an) with the 9-min run distance (yds) predicted peak V02 values with the mst accuracy and practicality in ml/kg/min- (R=O.7 89) and 1 'min- (R-0.966) : Peak k (ml/kg/min-l) = -12.13 t 0.29608 (X3) - 2 Peak yo2 (1-min-l) = -3.391 + 0.017377 (X3)+ 0.00072169 (XI) + 0.033712 (X2) Key: X1 = 9-min run distance (yds) X2 = wt (kg) X3 = Ht (cm) The multiple R value (0.812) which combined % fat with the 9-min was also concluded to be a goad predictor of peak V02 (ml/kg/min-1).
Keywords: Oxygen in the body; Running -- Physiological aspects